Comparison of indirect haemagglutination test and enzyme-linked immunosorbent assay for detection of serum antibodies to Pasteurella multocida in bovines - MAHANTESH, MAHANTESH; SINHA, D K; SINGH, V P (The Indian Journal of Animal Sciences, 2013)
Haemorrhagic septicaemia (HS) is an acute and fatal disease of cattle and buffaloes caused by Pasteurella multocida serotype B:2. The present study was undertaken to detect the antibodies to P. multocida by indirect haemagglutination assay (IHA) and indirect enzyme-linked immunosorbent assay (I-ELISA) and their results were compared. Serum samples (1,010) were collected from Assam, Karnataka, Odisha, Punjab, Tamil Nadu, Uttarakhand and Uttar Pradesh of India. An overall seroprevalence of 5.74 and 18.61% was observed by IHA and I-ELISA, respectively. Breed-wise, Hallikar (14.28%) and Khillari (50%) showed highest seroprevalence by IHA and I-ELISA, respectively. Sex and agewise, there were no significant differences in seroprevalence rates between male and female and different age groups by both tests. Source-wise, the I-ELISA detected the maximum seroprevalence (74.60%) in Cattle Breeding Farm, Hosur, Tamil Nadu while the IHA detected 21.62% in Sona Farm, Udhamsingh Nagar, Uttarakhand. The I-ELISA had a relative sensitivity and specificity of 94.83 and 86.03%, respectively in comparison to IHA. Concordance value showed an agreement in results of 86.53% between IHA and ELISA, which was further corroborated by the results of kappa statistics indicating a moderate agreement between these 2 tests.